Changing Management of Hematological Malignancies With COVID-19: Statement and Recommendations of the Lebanese Society of Hematology and Blood Transfusion - Ibrahim, Ahmad; Noun, Peter; Khalil, Charbel; Taher, Ali (Frontiers in Oncology, 2021)
COVID-19 caused by SARS-Cov-2 is a devastating infection in patients with hematological malignancies. In 2018, the Lebanese Society of Hematology and Blood Transfusion (LSHBT) updated guidelines for the management of hematological malignancies in Lebanon. Given the rapidly changing evidence and general situation for COVID-19, the LSHBT established some recommendations and suggestions for the management of the patients with hematological malignancies taking into account the Lebanese condition, economic situation, and the facts that SARS-Cov-2 infection has apparently been less devastating. In this article we present recommendations and proposals to reduce or to manage SARS-Cov-2 infection in the patients with myeloid hematological malignancies particularly acute myeloid leukemia, myelodysplastic syndromes, chronic myelogenous leukemia and other myeloproliferative neoplasms.